PA 04-2-0455 Qing-qi rickshaw: a boon or bane for public transportation? a study of road traffic injury patterns involving qing-qi rickshaws in karachi pakistan. (November 2018) - Muzzammil, Muhammad; SaeedMinhas, Muhammad; Effendi, Jahanzeb; Jahanzeb, Syed; Ovais, Muhammad; Mughal, Ayesha; Qadir, Abdul
Abstract : Objective: This study aims to describe the crash characteristics and injury patterns for Qingqi rickshaw occupants and other road users hit by Qing-qi rickshaw in Karachi, Pakistan. Method: An Observational/Descriptive study was conducted at Accident and Emergency and Orthopaedic Surgery Department, Jinnah Post Graduate Medical Center, Karachi Pakistan from July 2014 to June 2015.All patients who came with Qing-qi rickshaw accident in A and E of JPMC were included. Crash characteristics, details of injuries, injury severity parameters and outcome were documented in detailed interviews. Results: 486rickshawrelated injuries were noted in road traffic accidents by Qing-gi rickshaw. Age range was 2 to 85 years, mean age was 43.5 (SD 58.68). 350 injured victims were males and 136 were females. By occupation most victims were laborers and daily wageworkers (45%) and students (21%). Overloading of vehicle with more than two passengers was found in (28.5%). The most common cause of injury was collision with a moving vehicle (56%), followed by fall from rickshaw. The most common contributing factor was the overloading of rickshaw and roll over on turning(61%). Injury severity on arrival were mild (49%), moderate were (32%), and severe were (19%). Injuries related to head and neck (26%), face (14%), thorax and abdomen (5%), lower extremity and pelvic girdle (31%) and upper extremity (23%) were observed. Conclusion: This study concluded that Qing-qi rickshaw injuries are common and these vehicles are vulnerable to road traffic accidents. Occupants and road users are both at risk of injuries. Urgent preventive measures targeted towards this group are needed to reduce injuries involving rickshaws which results in increasing morbidity and mortality. The need for improved understanding of the risk characteristics of Qing-qi rickshaw is emphasized. The option of a safe, accessible and dignified mass transit system for the city of Karachi should be explored at the earliest.